Thermodynamic analysis and experimental verification of interface reactions of iron aluminide/tetragonal zirconia composite. (February 2014) - Li, J.; Li, Y.; Ma, R.; Song, Y.; Kong, C.; Song, P.
Abstract : This paper described the thermodynamic analysis and experimental verification of interface reactions between iron aluminide intermetallic and tetragonal zirconia. Thermodynamic analysis confirmed that chemical reactions between Fe–Al intermetallic and ZrO2 (3 mol.–%Y2 O3 stabilised zirconia) mainly depended on the Al content in Fe–Al intermetallic. For ZrO2 (3Y)/Fe3 Al composite, the interface reactions to form Al2 O3 and ZrAl2 would take place when Al content was >40 at-% in Fe–Al intermetallic, while no interface reaction occurred when using Fe3 Al as toughening phase. ZrO2 (3Y)/Fe3 Al composite was synthesised by hot press sintering to further verify the thermodynamic analysis of interface reactions between iron aluminide intermetallic and tetragonal zirconia. The phase composition, morphology and interface structure of ZrO2 (3Y)/Fe3 Al were investigated by X-ray diffraction, SEM and TEM. The results show that Fe3 Al was thermodynamic stable in ZrO2 (3Y) matrix, which was in good agreement with thermodynamically analysis.